COVID-19 impacts on tourism: Southern Africa’s experiences - Musavengane, Regis; Leonard, Llewellyn (Routledge, 2022)
Coronavirus (COVID-19) has negatively affected the tourism sector globally. Its impacts left destinations, organisations and communities in a distressed state, a situation which led to calls for new approaches that ensure the resilience, continuity and growth of distressed tourist destinations in a crisis environment. Most of the Southern African destinations have been in a distressed state due to the long-existing social, economic and political challenges. High urbanisation, environmental injustices, inequalities, social ills, corruption and unbalanced development policies are manifestations of these challenges. These were exacerbated by COVID-19. In Southern African countries afflicted by the pandemic, there is a high level of economic uncertainty, with sectors like tourism particularly hard hit. Nevertheless, the region has a number of positive tourism developments. The region hosts vast flora and fauna, including the big five wildlife, two of the Seven Wonders of the World, the Victoria Falls and Table Mountain. The region is a key player in the global tourism sector, from transportation, accommodation, and restaurants to recreational facilities. A significant number of people in the region depend on the sector for their livelihood. To examine COVID’s impact on tourism, this issue brings together five dynamic articles and one book review on the impact of COVID-19 in Southern Africa. To set the tone of the current issue, at the onset of COVID-19 in the region, Musavengane, Leonard and Mureyani, in their article titled ‘Doing tourism in Southern Africa amid the coronavirus pandemic: Navigating political, socio-economic and environmental inequalities’, provided pointers on possible areas that were to be affected heavily by COVID-19. Developing strategies for recovering from the damages caused by the pandemic will require a clear understanding of the relationship between the coronavirus and tourism. This article focused on five themes: (1) market potential, (2) health-related considerations, (3) social impacts, (4) environmental impacts, and (5) issues related to politics that could impact on regional integration. It concluded by posing critical questions for further research. For example, can Africa develop or provide medical solutions to the COVID-19 pandemic? What is the role of faith-based solutions to COVID-19 and economic growth? Is domestic tourism the best avenue to start opening up the tourism sector? What are Africans’ perceptions of foreign tourists in light of an imported or foreign disease? What is the way forward to promote good tourism governance in a crisis? Would virtual tourism be beneficial to the industry?